2019
DOI: 10.1063/1.5084235
|View full text |Cite
|
Sign up to set email alerts
|

High-enthalpy models for boundary-layer stability and transition

Abstract: The prediction of the transition dynamics of high-enthalpy boundary-layer flows requires appropriate thermodynamic and transport models. This work quantifies the influence of transport, diffusion, collision, equilibrium, and chemical-kinetics modeling on the stability characteristics and the estimated transition-onset location of canonical boundary layers. The computed behavior of second-mode instabilities is consistently highly dependent on the base-flow’s boundary-layer height. The Blottner-Eucken-Wilke tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…This is what was observed by Miró Miró et al. (2019 a ), who reported an underprediction by 38 % of the expected transition-onset location when employing the BEW transport model (appendix A.2) instead of the state-of-the-art CE model (appendix A.1).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This is what was observed by Miró Miró et al. (2019 a ), who reported an underprediction by 38 % of the expected transition-onset location when employing the BEW transport model (appendix A.2) instead of the state-of-the-art CE model (appendix A.1).…”
Section: Resultssupporting
confidence: 81%
“…This comparison also assesses whether the strong dependency of the predictions on the transport model, observed by Miró Miró et al. (2019 a ), extends to more complex physical scenarios.
Figure 1.Sketch of the various physical phenomena under consideration.
…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent work on hypersonic boundary layers by Miró Miró et al. (2019) has further shown the influence of using different high temperature TTP models on LST results. The integration of equilibrium chemistry in parabolized stability equations by Zanus, Miró Miró & Pinna (2019) revealed different effects depending on the instability mode considered.…”
Section: Introductionmentioning
confidence: 99%
“…The transport model was seen to be the one mostly conditioning such predictions: Miró Miró et al. (2019) reported that a transport model with a 10 % error with respect to the state of the art could lead to the prediction of a 38 % sooner transition onset location. Klentzman & Tumin (2013) investigated the receptivity and stability of boundary layers with a dissociating binary oxygen mixture, assuming viscous and inviscid perturbations.…”
Section: Introductionmentioning
confidence: 99%